Implikasi Pemberian Gift Live Pada Aplikasi Tiktok Perspektif Hukum Ekonomi Syariah - Nabila Sanpuri Afifah; Nurnazli; Miswanto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The development of the live streaming feature on TikTok with its gift system has created new patterns in digital economic transactions that raise issues under Islamic economic law, such as unclear contracts, potential gharar (unclear risk), and consumptive behavior. This study aims to examine the implications of gift-giving from the perspective of Islamic economic law and assess its compliance with Islamic muamalah principles. The method used was qualitative, with a field research approach and descriptive analysis through interviews, observations, and documentation of creators and viewers. The results show that gifts are understood as voluntary giving, resembling digital grants. However, there is still a tendency for excessive consumption and unclear motives among some users. From a sharia perspective, this practice is permissible as long as it fulfills the elements of willingness, clarity of purpose, and does not violate sharia provisions. Therefore, increasing sharia economic literacy is necessary to make digital practices more transparent and in accordance with Islamic principles.